Detection of real-time patterns in breaststroke swimming - Oliveira, C.; Santos, J.; Companico, J.; Jonsson, G. K. (Biomechanics and Medicine in Swimming X, 2006)
The objective of this research was to search for a particular type of repeated behaviour patterns in swimming movement cycles. The search used a new data analysis approach based on a process known as T-Pattern detection of the temporal and sequential structure of a given data set. The temporal patterns can be related to performance specific actions (e.g. comparison intracycle movement patterns similar to the one described by Coleman at al., 1998). Theme can be used for the analysis by using the relevant types of swimming T-data files created with ThemeCoder or other qualitative codification set. Certain breaststroke patterns of swimmers were detected, demonstrating the changes the swimmer had introduced in each swimming cycle. Coaches could possibly use this kind of structural information's when in need of optimizing the swimmer performance or find the particular hidden patters in swimming behaviour.